2010
DOI: 10.1007/s11136-010-9586-8
|View full text |Cite
|
Sign up to set email alerts
|

Are youth BMI and physical activity associated with better or worse than expected health-related quality of life in adulthood? The Physical Activity Longitudinal Study

Abstract: Youth overweight conveyed a long-term positive impact on several aspects of adult HRQL, and this impact may be both direct and indirect through BMI change and the effect on adult BMI. Youth PA had no long-term impact on adult HRQL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 45 publications
4
42
1
1
Order By: Relevance
“…A secondary aim of this study was to explore between-group differences in behavioral impulsivity. Considering the link between BMI and poorer psychosocial functioning across multiple domains, 47 including emotional impulsivity, 48 individual differences in participants' BMI were controlled in these analyses. Increased depressive symptomatology has also been linked to greater behavioral impulsivity, [49][50][51] and it was therefore included as a covariate in analyses of the secondary aim.…”
Section: Summary and Aimsmentioning
confidence: 99%
“…A secondary aim of this study was to explore between-group differences in behavioral impulsivity. Considering the link between BMI and poorer psychosocial functioning across multiple domains, 47 including emotional impulsivity, 48 individual differences in participants' BMI were controlled in these analyses. Increased depressive symptomatology has also been linked to greater behavioral impulsivity, [49][50][51] and it was therefore included as a covariate in analyses of the secondary aim.…”
Section: Summary and Aimsmentioning
confidence: 99%
“…Several studies suggest that persons with obesity tend to have psychosocial impairment and a poorer quality of life than do lean individuals. It has also been shown that impairments to quality of life worsen as obesity increases, with a greater effect on the physical dimensions of HRQoL than on the emotional aspects (e.g., Doll, Petersen, & StewartBrown, 2000;de Zwaan, Petersen, Kaerber, Burgmer, Nolting, Legenbauer, et al, 2009;Herman, Hopman, & Craig, 2010). Moreover, in those with obesity who seek treatment, weight loss, not increased fitness, contributes significantly to improvement in HRQoL (de Zwaan, et al, 2009;Ross, Milsom, Rickel, DeBraganza, Gibbons, Murawski, et al, 2009;Yancy, Almirall, Maciejewski, Kolotkin, McDuffie, & Westman, 2009).…”
mentioning
confidence: 99%
“…According to published reports, obese adolescents are more likely to become obese adults (5) , while being overweight during youth could have a negative impact on health-related quality of life in the future (14) . Previous data from Cyprus (with regards the year 2007) reported an adolescence obesity prevalence of 8.2% in males and 3.4% in females (7) .…”
Section: Discussionmentioning
confidence: 99%